Estimated economic damage of cardiac deaths in Tehran due to NO2 gas - Atieh Panahi; Fathollah Ommi; Yusef Rashidi (علوم محیطی)
Introduction: Air pollution can have devastating short- and long-term consequences on human health in different ways (Dehghani, 2007). The vulnerability of individuals to air pollution varies. Some diseases, such as asthma and pulmonary heart disease, are exacerbated by air pollution while it can also effect foetal development and lowers child IQ (Ghiasiddin, 2006). The statistics show that the number of patients who visit the emergency departments due to high blood pressure and heart attacks significantly increases on polluted days in Tehran. The costs of polluted air on health care run to billion dollars per year (Esfahanian, 2013).Materials and methods: This goal of this study was to determine economic cost of the impact of NO2 pollution in Tehran’s air on cardiovascular death using health effect determination software. Firstly, primary data was gathered from responsible organizations. Then, this volume based data (ppb) was converted into mass based data (g/m3) and the required data, such as the number of polluted days at various concentrations of NO2 and its yearly average in winter and summer, annually percentile and data from air pollution control stations with maximum and minimum values were extracted. Based on this data, AirQ software results showed the number of cardiovascular deaths due to NO2 pollution. These results were then compared with data from Behesht-e Zahra (Tehran’s main cemetery) and the consequent economic cost calculated using three methods of VSL, blood atonement and income.Result and discussion: Results indicating that cumulative cardiovascular deaths due to NO2 pollutant in 2013 numbered 827.3 cases of which 348.2 were women, 451.7 were men and 4.26 were children. The total average age of all cases was 51.9 which, if reduced from life expectancy in Iran which has reached 73 years, shows that the lost life expectancy due to NO2 pollution reached to 21.1 years in 2013. Economic costs imposed by bloodatonement were calculated at 7.41011 Rials on the cumulative frequency which shows the total cumulative cardiac mortality in 2013 which, therefore, was estimated as 80,450,665,000 Rials at concentrations between 90-99 g/m3 with the maximum number of cardiac deaths (between 10 > to 400 ≤). The results obtained from the VSL method show 9,431,220,000,000 Rials for total cumulative cardiac mortality in 1392 and 1,020,300,000 Rials for 90-99 g/m3 concentrations of NO2. Based on the income method results, the amount was calculated as 61011 Rials (for cumulative frequency) and 6/51010 Rials (at 90-99 g/m3 of NO2 concentration).Conclusion: In general, according to the results, the majority of cardiovascular deaths due to NO2 pollution were related to concentrations of between 90-99 g/m3. Furthermore economic costs calculated using the VSL method were greater than by the other mentioned methods